After the whale : Melville in the wake of Moby-Dick - Davis, Clark (University of Alabama Press, 1995)
After the Whale contextualizes Herman Melville's short fiction and poetry by studying it in the company of the more familiar fiction of the 1850s and 1890s. The study focuses on Melville's vision of the purpose and function of language from Moby-Dick through Billy Budd with a special emphasis on how language - in function and form - follows and depends on the function and form of the body, how Melville's attitude toward words echoes his attitude toward flesh.